Olympic values and Youth Olympic Games: a review study of scientific publications - Alves Medeiros, A. G.; Proença Garcia, R.; Silva dos Santos, D.; Silva Valente, J. A. (Olimpianos - Journal of Olympic Studies, 2020)
This study aims to present scientific productions that address the theme of the values of Olympism in the Youth Olympic Games. Therefore, a search was performed in the following databases: EBSCO, SportDiscus, Scopus, Web of Science, SciELO and Journal`s Portal CAPES/MEC, and five papers were selected for analysis. Given the recent history of Youth Olympic Games, the scarcity of studies in the area is understandable, especially regard to the axiological dimension of the event. However, the articles presented a methodological diversity, which allowed to identify relevant data about Olympic values in the Youth Olympic Games. It was found from the analyzed articles that, in general, the Games enable the knowledge and experience of Olympism, namely through the two supportive programs: Sports Programme and the Education and Culture Programme. Nevertheless, there is a lag in the spread of values out of Olympic schedule.